1999
DOI: 10.1097/00006123-199909000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Transcranial Doppler Investigation of Aneurysmal Vasospasm with Digital Subtraction Angiographic and Clinical Findings

Abstract: This study suggests that the MFV at the M1 segment is inadequate for estimation of the severity of VSP extending to vessels more peripheral than the M1 segment. Furthermore, severe VSP extending to more peripheral sites can produce more serious ischemic insults, compared with that localized to basal vessels. Patients with negative TCD results and clinical features suggesting the development of VSP should undergo quantitative investigation of cerebral circulatory parameters, such as the CCT, using intra-arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Tolonen reported in 1981 increased regional CCTs in ischemic brain hemispheres of 183 acute stroke patients by 99m-Technetium scintigraphy [6]. In more recent angiographic studies, a prolonged global CCT was shown to be associated with cerebral vasospasm after aneurysmal subarachnoid haemorrhage [7, 8]which can be reversed by intraarterial papaverine infusion [9]. A further clinical application of a regional angiographic CCT in cerebral AVM, analysing contrast in- and outflow pattern of the feeding and draining AVM vessels is currently under investigation [10, 11].…”
Section: Discussionmentioning
confidence: 99%
“…Tolonen reported in 1981 increased regional CCTs in ischemic brain hemispheres of 183 acute stroke patients by 99m-Technetium scintigraphy [6]. In more recent angiographic studies, a prolonged global CCT was shown to be associated with cerebral vasospasm after aneurysmal subarachnoid haemorrhage [7, 8]which can be reversed by intraarterial papaverine infusion [9]. A further clinical application of a regional angiographic CCT in cerebral AVM, analysing contrast in- and outflow pattern of the feeding and draining AVM vessels is currently under investigation [10, 11].…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Patients were considered to have vasospasm if there was evidence of arterial narrowing compared with the normal vessel caliber (mild Ͻ30%, moderate 30% to 60%, or severe 61% to 99%) as determined by 1 of 3 attending neurointerventional radiologists. Follow-up CT scans in a subset of 235 subjects were reviewed by a trained stroke neurologist (N.U.K., P.R.).…”
Section: Measurement Of Vasospasm and Clinical Risk Factorsmentioning
confidence: 99%
“…We eventually analyzed data from 26 studies. [3][4][5]7,10,11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] An exact quantification of the number of included patients and the number of tests performed was impossible, because there was inconsistency in reporting these numbers in the original studies. We contacted the main authors of 2 studies by letter to clarify queries about the reported data, but we did not receive any answer.…”
Section: Included and Excluded Trialsmentioning
confidence: 99%